SEROPREVALENCIA DEL VIRUS DE LARINOTRAQUEITIS INFECCIOSA EN BOVINOS CRIOLLOS DE PARINACOCHAS, AYACUCHO - Zacarías R., Erik (2002)
The seroprevalence of Bovine Herpes Virus-1, the etiological agent of Infectious Bovine Rinotracheitis, was evaluated in criollo cattle from the districts of Coracora, Chumpi, Puyusca and Pullo of the Parinacochas Province, Ayacucho. A total of 469 serum samples from 25 herds were tested by virus neutralisation test to detect neutralizing antibodies. The 67 .6 ± 4.2% (317 /469) of the samples had antibodies against BHV-1. The seroprevalence of the virus was similar in the animals of the 4 districts under evaluation. The antibody titers ranged from 2 to >256. Ali sampled herds had seroreactive animals. The study reported the presence of the BHV-1 in criollo cattle of the Parinacochas province, with a higher prevalence than the described in dairy herds in the country.